Crossing the Blood–Brain Barrier: Recent Advances in Drug Delivery to the Brain - Patel, Mayur M.; Patel, Bhoomika M. (CNS drugs, 2017)
CNS disorders are on the rise despite advancements in our understanding of their pathophysiological mechanisms. A major hurdle to the treatment of these disorders is the blood–brain barrier (BBB), which serves as an arduous janitor to protect the brain. Many drugs are being discovered for CNS disorders, which, however fail to enter the market because of their inability to cross the BBB. This is a pronounced challenge for the pharmaceutical fraternity. Hence, in addition to the discovery of novel entities and drug candidates, scientists are also developing new formulations of existing drugs for brain targeting. Several approaches have been investigated to allow therapeutics to cross the BBB. As the molecular structure of the BBB is better elucidated, several key approaches for brain targeting include physiological transport mechanisms such as adsorptive-mediated transcytosis, inhibition of active efflux pumps, receptor-mediated transport, cell-mediated endocytosis, and the use of peptide vectors. Drug-delivery approaches comprise delivery from microspheres, biodegradable wafers, and colloidal drug-carrier systems (e.g., liposomes, nanoparticles, nanogels, dendrimers, micelles, nanoemulsions, polymersomes, exosomes, and quantum dots). The current review discusses the latest advancements in these approaches, with a major focus on articles published in 2015 and 2016. In addition, we also cover the alternative delivery routes, such as intranasal and convection-enhanced diffusion methods, and disruption of the BBB for brain targeting.